Improving the Assessment of Implicit Motives Using IRT: Cultural Differences and Differential Item Functioning. Issue 4 (4th July 2019) - Runge, J. Malte; Lang, Jonas W. B.; Chasiotis, Athanasios; Hofer, Jan
ABSTRACT: Researchers have long been interested in studying differences in implicit motive between different groups. Implicit motives are typically measured by scoring text that respondents have written in response to picture cues. Recently, research on the measurement of implicit motives has made progress through the application of a dynamic Thurstonian item-response theory model (DTM; Lang, 2014 ) that captures 2 basic motivational processes in motivational research: motive competition and dynamic reduction of motive strength after a motive has been acted out. In this article, the authors use the DTM to investigate differential item functioning (DIF) in implicit motive measures. The article first discusses DIF in the context of the DTM. The authors then conduct a DIF analysis of data from a study that used a picture set of the Operant Motive Test (OMT; Kuhl & Scheffer, 2002) with participants from Cameroon, Germany, and Costa Rica. Results showed no evidence of DIF in 9 pictures and some evidence for DIF in 3 pictures. The authors show a partial invariance model can be specified and use this partial invariance model to study latent mean differences between Cameroon, Germany, and Costa Rica. The discussion focuses on the use of IRT DIF methods in future research on implicit motives.